Specific HLA types are associated with antiepileptic drug-induced Stevens-Johnson syndrome and toxic epidermal necrolysis in Japanese subjects - Kaniwa, Nahoko; Sugiyama, Emiko; Saito, Yoshiro; Kurose, Kouichi; Maekawa, Keiko; Hasegawa, Ryuichi; Furuya, Hirokazu; Ikeda, Hiroko; Takahashi, Yukitoshi; Muramatsu, Masaaki; Tohkin, Masahiro; Ozeki, Takeshi; et al. (Pharmacogenomics, 2013)
This preliminary study investigated genomic biomarkers for Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), related to three antiepileptic drugs, zonisamide, phenobarbital and phenytoin. class I and loci were genotyped for Japanese patients with zonisamide-, phenobarbital- or phenytoin-induced SJS/TEN (n = 12, 8 and 9, respectively) and for healthy Japanese volunteers (n = 2878). Carrier frequencies of in patients with zonisamide-induced SJS/TEN and in the general Japanese population were 41.7 and 6.81%, respectively. Carrier frequencies of in patients with phenobarbital- and phenytoin-induced SJS/TEN and in controls were 75.0, 55.6 and 15.2%, respectively. and , in a dominant model, were significantly associated with zonisamide- and phenobarbital-induced SJS/TEN, respectively (Pc = 0.0176 and 0.0042, respectively). Our data suggest that and are potential biomarkers for zonisamide- and phenobarbital-induced SJS/TEN, respectively, in Japanese individuals. Original submitted 25 April 2013; Revision submitted 11 September 2013